Effects on rumen microbiome and milk quality of dairy cows fed a grass silage-based diet supplemented with the macroalga Asparagopsis taxiformis - Krizsan, Sophie J.; Ramin, Mohammad; Chagas, Juana C. C.; Halmemies-Beauchet-Filleau, Anni; Singh, Abhijet; Schnürer, Anna; Danielsson, Rebecca (Frontiers in Animal Science, 2023)
The objective was to determine the effects on rumen microbiome and milk quality when reducing methane (CH4) produced from enteric fermentation by the addition of Asparagopsis taxiformis to diets of dairy cows. Six Nordic Red cows at 122 ± 13.7 (mean ± SD) days in milk, parity 2.7 ± 0.52 and producing 36 ± 2.5 kg milk/d at the start of the trial were blocked by milk yield, and assigned to an extra period Latin square change-over design comprising two dietary treatments. An extra period of observation was added to the Latin-square change-over design in order to control carry-over effects, and the whole experimental pattern was replicated once. The dietary treatments were either a diet consisting of grass silage and a commercial concentrate mixture (60:40) not supplemented or supplemented with 0.5% of Asparagopsis taxiformis (AT) on organic matter intake basis. On average daily CH4 production, CH4 yield, and CH4 intensity decreased by 60%, 54%, and 58%, respectively for cows fed the diet supplemented with AT. Further, hydrogen gas emitted by cows fed diets supplemented with AT increased more than 5 times compared to cows fed a non-AT supplemented diet. Fed intake was decreased and milk production altered reflecting a decreased yield of milk fat for cows fed AT supplemented diet, but feed efficiency increased. Rumen fermentation parameters were changed to promote a propionate rather than acetate and butyrate fermentation. The most prominent change in milk quality was an increase in bromine and iodine when the diet was supplemented with AT. The reduction of CH4 was associated with a shift from Methanobrevibacter to Methanomethylophilaceae in archaeal population population and a lower abundance of Prevotella in bacterial population. Changes in milk fat odd- and branched chain fatty acids in the current study with AT supplementation support observed differences in ruminal archaeal population.